EFSA International Workshop on RA of Combined Exposure to Multiple Chemicals. Issue 7 (22nd July 2022) - ,; Dorne, Jean‐Lou CM; Hogstrand, Christer; Dujardin, Bruno; Kass, George EN; Liem, AK Djien; Tarazona, Jose; Machera, Kyriaki; Robinson, Tobin; Manini, Paola; Benfenati, Emilio; te Biesebeek, Jan Dirk; et al.
Abstract: Human Risk Assessment (RA) of combined exposure to multiple chemicals follows the steps of RA namely problem formulation, exposure assessment, hazard assessment and risk characterisation. Over the last decade, scientific advisory bodies have published a range of harmonised guidance documents to provide practical approaches for risk assessors. These include the WHO, the US‐EPA, the Joint Research Centre (JRC) of the European Commission, the OECD and the recent EFSA MIXTOX guidance document dealing with harmonised methodologies for the human health, animal health and ecological RA areas. On May 21 st 2021, the Scientific Committee of EFSA published a draft guidance document on scientific criteria to group chemicals in assessment groups using hazard‐driven criteria and prioritisation methods using exposure‐driven and risk‐based approaches. The latter guidance and future challenges were the topic of this international workshop which was held online in the afternoons of the 18 th, 19 th and 20 st October 2021. First, a plenary session provided overviews of European and international activities in the field including WHO, OECD, US‐EPA, JRC and EFSA. With a total of 118 participants including national and international scientific advisory bodies, academics and researchers, NGOs, industry, risk assessors, risk managers, four discussions groups were created for three break‐out group sessions: 1) Hazard‐driven criteria for grouping multiple chemicals into assessment groups; 2) Exposure‐driven and risk‐based criteria for the prioritisation of multiple chemicals 3) Data gaps and future challenges for human health and environmental RA of combined exposure to multiple chemicals to identify priority topics of international relevance and a way forward to address these topics. A final discussion and wrap‐up session concluded the meeting. This event report provides a summary of the discussions together with conclusions and recommendations.